Tumor Necrosis Factor α–Induced MicroRNA‐18a Activates Rheumatoid Arthritis Synovial Fibroblasts Through a Feedback Loop in NF‐κB Signaling. Issue 4 (28th March 2013) - Trenkmann, Michelle; Brock, Matthias; Gay, Renate E.; Michel, Beat A.; Gay, Steffen; Huber, Lars C.
Abstract: Objective: To elucidate whether the microRNA (miRNA) cluster miR‐17–92 contributes to the activated phenotype of rheumatoid arthritis synovial fibroblasts (RASFs). Methods: RASFs were stimulated with tumor necrosis factor α (TNFα), and the expression and regulation of the miR‐17–92 cluster were studied using real‐time quantitative PCR (PCR) and promoter activity assays. RASFs were transfected with single precursor molecules of miRNAs from miR‐17–92 and the expression of matrix‐degrading enzymes and cytokines was measured by quantitative PCR and enzyme‐linked immunosorbent assay. Potential miRNA targets were identified by computational prediction and were validated using reporter gene assays and Western blotting. The activity of NF‐κB signaling was determined by reporter gene assays. Results: We found that TNFα induces the expression of miR‐17–92 in RASFs in an NF‐κB–dependent manner. Transfection of RASFs with precursor molecules of single members of miR‐17–92 revealed significantly increased expression levels of matrix‐degrading enzymes, proinflammatory cytokines, and chemokines in precursor miR‐18a (pre‐miR‐18a)–transfected RASFs. Using reporter gene assays, we identified the NF‐κB pathway inhibitor TNFα‐induced protein 3 as a new target of miR‐18a. In addition, pre‐miR‐18a–transfected RASFs showed stronger activation of NF‐κB signaling, both constitutively and in response to TNFα stimulation. Conclusion: Our data suggest that the miR‐17–92–derived miR‐18a contributes to cartilage destruction and chronic inflammation in the joint through a positive feedback loop in NF‐κB signaling, with concomitant up‐regulation of matrix‐degrading enzymes and mediators of inflammation in RASFs.